Social Media Addiction as Predictor of Academic Procrastination among Undergraduates of University of Ilorin, Nigeria - Olusegun, BADA, Steve; AMINU, Adamu Idris (International Journal of Educational Management, 2025)
The study examined the relationship between social media addiction and academic procrastination among undergraduate students of University of Ilorin, Ilorin, Nigeria based on religion and gender. The study adopted a descriptive-survey design. The population for the study consisted of all the 3,874 four hundred level students in the three selected faculties (Faculty of Education, Faculty of Communication and Information Science and Faculty of Social Sciences) one hundred and fifty (150) undergraduate students were purposively selected from three faculties as respondents for the study. Research instruments titled “Social Media Addiction Questionnaire SMAQ” and “Academic Procrastination Questionnaire (AAP)” were used for data collection. The instruments were validated by 2 experts in the field of Educational Psychology. Test re-test method was adopted to test the reliability of the instrument. Percentage and t-test statistics were used to answer the research question and test the generated hypotheses at 0.05 level of significance. The findings revealed that; there is a high level of academic procrastination among undergraduate students of University of Ilorin, Ilorin, Nigeria, there is a significant relationship between social media addiction and academic procrastination among undergraduate students of University of Ilorin, Ilorin, Nigeria. The study recommended that; parents, teachers and educational stakeholders should always call the attention of undergraduate students to the advantages and disadvantages of social media addiction which can lead to procrastination of academic activities, parents should always check on their children and wards to encourage them to spend quality time on academic task and there should be regular and adequate sensitization of undergraduate students on the proper usage social media.